Digital Marketing With Career Transformation Using Marketing Strategy 5.0 With Artificial Intelligence - Rahmadani, Fitria; Nugroho, Rusdi Hidayat (CV. Lenggogeni Data Publishing, 2025)
The development of Artificial Intelligence (AI) technology today has brought significant influence on changes in digital marketing strategies in the marketing 5.0 era. This research aims to analyze 20 scientific articles related to the role of AI in digital marketing and its impact on career transformation. The research uses the method of literature review, strategies, and contributions of AI in the marketing field. The analysis shows that AI plays a significant role in personalization, marketing strategy, improving operational efficiency, and data-driven decision making. Marketing 5.0 provides new opportunities in career development, especially through the application of advanced technologies such as AI and Big Data. This research concludes that the adoption of AI in digital marketing not only changes the way companies interact with consumers, but also creates broader career transformation opportunities for individuals in this field. Keywords:Digital Marketing, AI, Big Data